RELATIONSHIP BETWEEN BODY CIRCUMFERENCES AND LUNG FUNCTION TESTS AMONG UNDERGRADUATE STUDENTS OF A NIGERIAN UNIVERSITY - Ojo, Ojoawo Adesola; SA, Adeniran; Fatiregun, Olubayo; Sunday, Onagbiye; Bamiwuye, Sina (Pakistan Journal of Physiology, 2013)
Background: The purpose of this study was to find out the relationship among some anthropometric variables and lung functional capacities of the undergraduate students in Obafemi Awolowo University (OAU), Nigeria. Method: This study was undertaken at the Department of Physical and Health Education, Faculty of Education, OAU, Ile Ife, Nigeria. One hundred and forty students (90 males and 50 females) of OAU participated in the study. Anthropometric variables measured were, height, weight and body circumferences at the waist, hip, thigh, calf, arm, and forearm a standard protocol. Spirometry was used to measure Tidal Volume (TV), Expiratory Reserve Volume (ERV), Inspiratory Capacity (IC), Vital Capacity (VC), and Total Lung Capacity (TLC). Data were analysed using descriptive statistics, independent t-test, and Pearson Product Moment Correlation. Results: There was a significant negative correlation between VC and weight (r= -0.190, p<0.05), thigh circumference (r= -0.241, p<0.001), WHR (r= 0.260, p<0.001), but a significant positive correlation between VC and height (r= 0.330, p<0.001), wrist (r= 0.300, p<0.001) and forearm circumference (r= 0.202, p<0.05). TLC had positive significant correlation with height (r= 0.643, p<0.001), forearm circumference (r= 0.176, p<0.05), and wrist circumference (r= 0.441, p<0.001), but negative significant correlation with BMI (r= -0.244, p<0.001). Conclusion: An increase in WHR and weight may reduce the VC and TLC. TLC could be reduced by an increase in BMI and a tall individual may have enhanced VC and TLC.